Transnational Legal Cooperation And Global Trade: Rethinking International Investment Law In The Era Of Sustainable Development - M. Munif; Bambang Wahrudin (Journal of Law, Policy and Global Development, 2025)
This article critically examines the role of international investment law (IIL) in supporting the objectives of sustainable development and global partnership, particularly under Sustainable Development Goal 17 (SDG 17). Historically, IIL has prioritized the protection of investors through strong legal guarantees and dispute settlement mechanisms, often at the expense of environmental protection, social equity, and the regulatory autonomy of host states. However, as the global development agenda shifts toward inclusivity, sustainability, and accountability, there is increasing recognition that investment treaties and legal regimes must evolve accordingly. This study employs a qualitative legal analysis of international treaties, case law, and policy frameworks to assess the emerging trends in IIL that reflect sustainability principles. Case studies from agreements such as the EU–Vietnam Investment Protection Agreement and reforms within UNCITRAL and ICSID illustrate the slow but important progress toward balancing investor rights with state responsibilities and global development goals. The article argues that transnational legal cooperation, legal harmonization, and inclusive treaty design are essential to creating an investment regime that not only facilitates global trade but also supports equitable and sustainable growth.